2014
DOI: 10.4097/kjae.2014.66.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Attention to postoperative pain control in children

Abstract: Even with the rapid development of pediatric postoperative pain management, pediatric patients have remained undertreated for postoperative pain because of difficulty in pain assessment and concerns regarding side effects of opioid analgesics. Although there are no perfect pain assessment techniques and no absolutely safe analgesics, proper monitoring and an individualized analgesic plan after due consideration of age, operative procedures, and underlying illness, using multimodal analgesics may improve the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
(54 reference statements)
0
27
0
4
Order By: Relevance
“…Local anesthetic or NSAID application during surgery delays post-operative pain and amount of required analgesic. Mainstay of post-operative pain management in children consists of regional or caudal block + intraoperative preemptive analgesia [37]. If pain continues at post-operative period despite them paracetamol+NSAID may be added.…”
Section: Drugs and Pain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Local anesthetic or NSAID application during surgery delays post-operative pain and amount of required analgesic. Mainstay of post-operative pain management in children consists of regional or caudal block + intraoperative preemptive analgesia [37]. If pain continues at post-operative period despite them paracetamol+NSAID may be added.…”
Section: Drugs and Pain Managementmentioning
confidence: 99%
“…Circumcision should be performed under general anesthesia in all age groups [37]. At post-operative period appropriate pain management should be provided [39].…”
Section: Circumcisionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its passage beyond acceptable limits is a common and costly experience (Coll et al, 2004) The process of post operative pain management is always initiated before the surgery is done and this is because, it has been realized that good pain prevention reduces the severity of pain felt after the surgery has been done. Even though there is fast progress in the management of postoperative pain in children, children who have under gone surgery do not have their pain after the surgery being well managed because of complexity in the evaluation of the child level of pain and also fear of the possible addictive effect of pain relievers that belong to the opiod group (Lee and Jo, 2014). It is agreed that it is a bit difficult to have a faultless pain assessment method for children and pain relieving medications that do not have any adverse effect at all on them but a good assessment of the child's pain and a good pain relieving approach designed by considering how young the child is, the kind of surgery that the child is to undergo, the kind of disease condition that the child had that necessitated the surgery with administration of a combination of the different pain relieving medications can improve the reduction of post operative pain in children (Lee and Jo, 2014) Research has proven that considerable pain stimulation devoid of appropriate analgesia, will not only cause intolerable pain at the time of the stimulation but will result in the production of 'pain memory' which subsequently produces an inflated response to any form of stimulated pain (Taddio A et al, 1994) (Taddio A et al, 1995) (Taddio A et al, 1997) Two decades ago, there was a survey that revealed that 40% of children that had undergone one kind or another surgical procedure felt moderate or severe postoperative pain and out of this group, 75% of them received analgesia that was not enough to control their pain (Marther L, Mackie J, 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efek samping tersebut harus menjadi pertimbangan dalam penatalaksanaan nyeri pascaoperasi. Oleh karena itu, penanganan nyeri pascaoperasi harus dilaksanakan secara bijak dengan memberikan pilihan terapi yang sesuai dengan derajat nyeri pasien 8,13,14.…”
unclassified